Perancangan Animasi Sejarah Komunitas Dayak Losarang - Hidayat, Rahman; Maulina, Rini (Fakultas Desain Universitas Komputer Indonesia, 2022)
The Losarang Dayak community has existed since 1970, and is still surviving today. This community has nothing to do with the Kalimantan Dayak Tribe. The Losarang Dayak are not a traditional tribe, but a pure community founded by Paheran Takmad Diningrat in Losarang Indramayu. Having different characteristics makes this community part of the uniqueness of the Indramayu community. Some of the people of Indramayu know the existence of this community but not its history, the importance of public knowledge about the history of this community to increase mutual respect and respect and increase public insight and knowledge about the life of the Losarang Dayak Community. Previously, there had been information media in the form of books that explained the history and life values of the Losarang Dayak community by Abdurrahman AL-Muhaili. However, the book was printed in limited and academic nature. Therefore, it is necessary to design additional information regarding the history of the Losarang Dayak Community with the aim of presenting information in visual form packaged through motion graphic animation media published on the youtube platform so that it is easily accessible, and conveyed to the target audience.